1988
DOI: 10.1111/j.1469-7998.1988.tb03748.x
|View full text |Cite
|
Sign up to set email alerts
|

Haematological studies on wild black rhinoceros (Diceros bicornis)‐evidence of an unstable haemoglobin

Abstract: With 1 figure in the text) Baseline haematological data were obtained through routine analyses of blood samples from 31 wild black rhinoceroses captured in the Mana Pools National Park, Zimbabwe. Additional tests showed that the haemoglobin of this population is unstable; this observation helps explain the attacks of acute intravascular haemolysis documented in captive animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1993
1993
1999
1999

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
1
0
0
Order By: Relevance
“…We observed that 10-15% of circulating erythrocytes in apparently normal rhinoceroses contained single large Heinz bodies, and others have made similar observations [19][20][21]. In two animals thus studied, exposure to acetylphenylhydrazine increased the percentage of cells containing multiple Heinz bodies to -90% within 30 min, but only to 25% if the cells had been preincubated with adenosine and glucose to increase their intracellular ATP (see below).…”
Section: Glutathione Stability and Hmp Shunt Metabolismsupporting
confidence: 77%
“…We observed that 10-15% of circulating erythrocytes in apparently normal rhinoceroses contained single large Heinz bodies, and others have made similar observations [19][20][21]. In two animals thus studied, exposure to acetylphenylhydrazine increased the percentage of cells containing multiple Heinz bodies to -90% within 30 min, but only to 25% if the cells had been preincubated with adenosine and glucose to increase their intracellular ATP (see below).…”
Section: Glutathione Stability and Hmp Shunt Metabolismsupporting
confidence: 77%